Factor Related to Hypertension Diet Compliance in Hypertensive Patients in The Working Area of The Batuceper Health Center Tangerang City - Ahmad Fikri Perangin Angin; Wasludin Wasludin (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Abstract Background: Hypertensive patients must always adhere to a hypertensive diet. A person's compliance can be influenced by many factors, some of which will be examined in this study. Purpose: Find out more about factors related to hypertension dietary compliance. : Method: This type of research is an analytical survey with a cross-sectional approach. The nonprobability sampling technique uses an accidental sampling method so that 87 samples are obtained. This study used univariate, and bivariate analysis using chi-square and multivariate using logistic regression. Results: The chi-square test found that the level of knowledge had a p-value of 0.018, age had a p-value of 0.771, gender had a p-value of 0.992, level of education had a p-value of 0.023, work had a p-value of 0.688 and family social support had a p-value of 0.007. The most dominant factor associated with dietary adherence to hypertension was family support with a p-value of 0.031 on multiple logistic regression tests and OR = 3.004. Conclusion: Factors related to adherence to a hypertension diet in the working area of ​​the Batuceper Health Center, Tangerang City, are level of knowledge, education, and family social support, with the most dominant factor being family social support.